Aplikasi Penjualan Mobil Pada Gocah Garage Berbasis Website Menggunakan Metode Flat Rate - Albin Setiawan; Supina Batubara; Barany Fachri (Jurnal Nasional Teknologi Komputer, 2026)
The process of car sales, especially credit-based transactions, requires accurate data management and precise installment calculations to support customer decision-making. Gocah Garage, as a car showroom that provides both cash and credit sales services, still performs installment simulations manually using calculators and spreadsheet applications, which is time-consuming and prone to calculation errors. This study aims to develop a web-based car sales application that implements the Flat Rate method to calculate credit installments accurately and efficiently. The research method used is a software development method with the Waterfall model, which includes requirement analysis, system design, implementation, and testing. The application is developed using HTML, PHP, JavaScript, and MySQL as the database. The results show that the developed system is able to manage car data, customer data, and sales transactions effectively, as well as automatically calculate monthly installments using the Flat Rate method. The application helps reduce calculation errors, speeds up the sales process, and improves service quality at Gocah Garage.